Evaluation of seed sett ages and stem segment position on sugarcane yield and yield related traits - Darika Bunphan; Ruchuon Wanna; Wanwipa Pinta; Chorkaew Aninbon; Goitseone Malambane (My University, 2024)
Sugarcane (Saccharum officinarum L.) plays a vital role in tropical and sub-tropical economies due to its high sucrose content, bioenergy potential, and drought resistance. This study aimed to comprehensively investigate the effects of different seed sett (seed material) ages and variations in stem position of the seed setts on both yield and yield related traits of sugarcane cv. Khon Kaen3 (KK3). The experiment was laid out by 3×3 factorial in randomized complete block design (RCBD) with three replications. Factor A represented sugarcane seed sett ages (8, 9 and 10 months old), factor B represented different stem positions where seed setts segments were sectioned out (basal, mid and top part) and- used as planting material (clones). Agronomic management was administered at recommended rates and the growth, development and yield traits were observed. The results showed that seed sett ages influenced the number of tillers at specific growth stages, while different segments affected leaf area (LA) and stalk fresh weight. Seed sett age and position showed significant interactions for some traits. Notably, juice yield was significantly affected by both seed sett ages and segments, with the combination of 10-month-old seed setts and the middle segment yielding the highest juice. Brix value, a crucial trait for sugar production, remained unaffected by these factors. Dry matter accumulation was inconsistent, with seed sett ages impacting stalk dry weight. In conclusion, the results showed that most growth and development traits were not influenced by seed sett ages and stem position segments, but most importantly juice yield at maturity was influenced by seed sett age and position of stem segments. These findings enhance our understanding of sugarcane cultivation practices, offering valuable insights for optimizing planting strategies in the sugarcane industry.
Keywords: Sugarcane Cultivation and Processing